DAYA TARIK GLAD2GLOW DI TIKTOK: BAGAIMANA BRAND AMBASSADOR, KUALITAS PRODUK, DAN HARGA MEMPENGARUHI MINAT BELI - Rahayu, Ni Putu Febri Lintang; Prawitasari, Putu Putri; Lestari, Ni Putu Nina Eka (LP2M Universitas Bina Bangsa, 2025)
This research was conducted to analyze the impact of brand ambassadors, product quality, and prices both separately and simultaneously on consumer buying interest. The sample used was taken from 114 consumers aged between 17 and 30 years old, living in Denpasar, and are active users of the TikTok Application. This research was conducted using the SPSS application version 26. This study shows that brand ambassadors have a positive influence on buying interest, as well as product quality which has a positive effect. In addition, price has also been proven to have a positive influence on buying interest. Simultaneously, brand ambassadors, product quality, and price have a significant influence on consumer buying interest. The percentage of the influence of independent variables on buying interest is 70.1%. The advice that researchers can share, namely Glad2Glow on the TikTok Application, is expected to collaborate with artists or influencers who understand Glad2Glow products, always be consistent in maintaining product quality, make price policies that are more competitive, and always bid on products according to the needs or desires of consumers and have good quality